Acknowledging the role of agriculture in a differentiated European countryside: example from a typology applied to Portugal - Pinto-Correia, Teresa (2012)
Rural landscapes in Europe are changing from strictly a space of production into also a space of consumption and of protection, in multiple transition processes, occurring at multiple scales. Portugal is a good example of these various processes going on, as it is naturally a country of biophysical contrasts and diversified landscapes, and it has both very dynamic and very fragile rural areas, areas with a strong farming sector and others with a very traditional and non competitive agriculture. In this country, a range of recent studies is showing an increasing differentiation in the development of rural areas, which develop at present along diverse trajectories. Some regions are developing very dynamically, but this can happen with or without a strong role of agriculture. Other regions are affected hard by marginalization processes, that raise concern as they are often related to issues such as the loss of socio-economical dynamics, the loss of cultural landscapes , land abandonment and decreasing biodiversity, and also physical desertification. In the meantime, these are the regions with landscapes most highly demanded for emerging non-commodity functions. The differential development of rural areas means no clear-cut relations between marginalization, abandonment and the loss of dynamics and diversity, can be identified. Neither a clear relation between a dynamic farming and a dynamic countryside. Therefore, a more detailed analysis of the different processes occurring and of their drivers and consequences is needed – so that new potentialities based on a territorial perspective, may be stressed. Separating the various components of the countryside that are under change leads to a more clear analysis of the processes going on. It is possible to develop a typology of rural areas, where the characteristics and trends of the rural landscapes and the functions (commodity and non commodity) they may secure can be assessed, but also the role that farming may play, if it the transition of perspectives from sectoral to territorial is fulfilled.